Risk factors for multiple primary squamous cell carcinomas of the oral cavity - SAITO, Tomokatsu; KAWABE, Ryoichi; KOBAYASHI, Sonou; OMURA, Susumu; FUJITA, Kiyohide; AOKI, Shinjiro (Japanese Journal of Oral and Maxillofacial Surgery, 1999)
Multiple primary cancers of the oral cavity are increasing and are considered animportant factor affecting the prognosis of oral cancer, but this condition is poorly understood. To investigate risk factors for this disease, we reviewed 200 patients with oral squamous cell carcinoma who were treated at the Department of Oral and Maxillofacial Surgery, Yokohama City University School of Medicine during the 5 years between 1992 and 1997. Twenty-nine patients (14.5%) had oral multiple primary cancer (14 synchronous and 8 metachronous), and 15 (7.5%) had multiple primary cancer of the upper digestive tract. Odds ratios (ORs) and 95% confidence intervals (CIs) were derived from logistic regression analysis, including sex, smoking, drinking, family history, mucosa adjacent to tumor, and oral leukoplakia. Oral leukoplakia (OR=4.6, C1=1.57-13.33) was associated with oral multiple primary cancer. The OR for women was 3.4 (C1=1.12-10.14) relative to men. A risk factor for the multiple primary cancers of the upper digestive tract was drinking (OR=5.1, CI=1.33-19.31). This study provides evidence that the risk factors for oral multiple primary cancers differ from those of multiple primary cancers of the upper gastrointestinal tract.